ChemInform Abstract: Metal‐Free [3 + 2] Oxidative Coupling of Phenols with Alkenes: Synthesis of Dihydrobenzofurans. Issue 6 (21st January 2016) - Zhao, Yating; Huang, Binbin; Yang, Chao; Li, Bing; Xia, Wujiong
Abstract: An environmentally benign and metal‐free [3+2]‐cycloaddition of phenols and styrenes with sodium persulfate as an oxidant affords dihydrobenzofurans.